Qualidade e propriedades mecânicas de milho em função da temperatura de secagem - Lacerda, Bruno de Oliveira (2023)
The objective of this study is to evaluate the effect of drying temperature on the physical and mechanical properties of corn grains. Alcohol production from this cereal plays a significant economic, agricultural, and social role in the state of Mato Grosso, becoming one of the main destinations for the crop produced in the region. Furthermore, the favorable climate of the state often allows the grains to dry naturally in the field, ensuring the obtainment of a better product quality. In the cultivation and processing of corn, drying proves to be an important step in the preservation process, as it removes moisture content, preventing deterioration, and extending its shelf life. It is relevant to consider this process as an integral part of grain production stages, especially when there is a need to accelerate the drying process through artificial means in various locations of the country, or when the ideal moisture content for the desired purpose or storage is not achieved. In this sense, drying temperature, as a critical factor in production, directly influences grain quality, affecting sensory characteristics such as texture, taste, color, aroma, and nutritional value; it can also interfere with enzymatic activity during alcohol fermentation processes. Efficient drying helps prevent the proliferation of unwanted microorganisms, such as pathogenic fungi, and minimizes the loss of essential nutrients. Therefore, understanding the importance of drying and its relationship with temperature is essential to ensure the quality of corn destined for production and consumption, contributing to food security, improving the final product, and satisfying consumers' needs.